Residual Heat Stress Improves Spatial Rotation Function, but does Not Modify Attention - Margarita Černych; Marius Brazaitis (Lithuanian Sports University, 2018)
Background. We aimed to evaluate the eﬀect on cognitive performance (spatial rotation ability, and working memory) after recovery from heat stress when body temperature naturally decreases to initial level. Methods. Whole body hyperthermia was induced with Finnish sauna bathing. Before (PRE) and 90 min after (POST) heat stress (EXP)/ rest (CON) participants assessed their own overall motivation, level of sleepiness and mood. Also Switching task with a combination of the Manikin (Man) and the Mathematical Processing (Math) test was performed. Results. Level of sleepiness signifcantly (p < .05) increased 90 min after sauna from 1.88 ± 0.30 (EXP PRE) to 3.44 ± 0.45 (EXP POST), but did not change signifcantly in CON (PRE 2.81 ± 0.53, POST 2.88 ± 0.30). Participants felt more fatigue (p < .05) during the POST measurements in both trials (CON 3.88 ± 0.79 and EXP 5.88 ± 1.03) compared with before values (CON 2.75 ± 0.66 and EXP 2.44 ± 0.87); 90 min after sauna fatigue was significantly higher (p < .05) in EXP compared with CON. During the EXP POST (1.49 ± 0.12 s) measurements response time in Man task signifcantly decreased (p < .05) compared with PRE (1.66 ± 0.16 s), and throughput signifcantly (p < .05)increased 90 min after sauna (EXP POST 42.09 ± 3.28) compared with before values (EXP PRE 38.96 ± 3.31). No other changes were found in Man ant Math task performance. Conclusion. Residual heat stress increases the level of sleepiness and induces higher feeling of fatigue, but that does not impair attention and concentration. Moreover, residual heat stress improves spatial rotation function. Keywords: heat stress, attention, working memory, fatigue, and sleepiness.